How School Nurses Can Benefit From Immunization Information Systems: Information Exchange to Keep Students in School and Ready to Learn. (March 2013) - Bobo, Nichole; Etkind, Paul; Martin, Kimberly; Chi, Alison; Coyle, Rebecca
Recorded and retrievable information from state immunization information systems (IIS)—previously known as immunization registries—benefits schools, students, families, state and local immunization programs, and the medical home. The National Association of School Nurses (NASN), the National Association of County and City Health Officials (NACCHO), the Association of State and Territorial Health Officials (ASTHO), and the American Immunization Registry Association (AIRA) support state IIS as a way to facilitate immunization compliance, prevent immunization duplications, and sustain high immunization rates. There is much variability from state to state on who can access and/or input data into the IIS. School nurses need to know they can pick up the phone and contact their state IIS, and state IIS personnel need to know that school nurses desire full access to their state registry to view records and record vaccines administered and/or documented by families.